Post a New Question


posted by .

I have a question, if f(x)=x/2 and g(x)=3x+1 find:

a) (f+g)(x) i know you go x/2+3x+1.
but how do i solve that??

b) (f-g)(x) i know you go x/2-3x+1,
how do i solve?

c)(f*g)(x) how do i solve?

(f/g)(x) how do i solve??

f(g(x)) how do i solve??
thanks for your itmeee


    for (f+g)(x) you would add up your two function expressions and simplify them

    so (f+g)(x) = x/2 + 3x+1
    = x/2 + (6x+2)/2 = (7x+2)/2
    which is not what you have

    suppose we use x=4
    f(4)= 4/2 =2
    g(4) = 13
    so (f+g)(4) = 15
    in my (f+g)(x) = (7x+2)/2
    (f+g)(4) = (7(4)+2)/2 = 15

    for (f-g)(x) you would subtract the two functions,
    for (f*g)(x) you would multiply them, etc

    test your answers in a similar way to the one I showed you


    thanks so much:)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question